Experiments with ultracold neutrons - Nesvizhevsky, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Ultracold neutrons (UCN) form a tiny low-energy fraction in Maxwelian spectrum of thermal neutrons in moderators of nuclear reactors and spallation sources. Their energy is extremely small ( 10–7 eV), their velocity is a few meters per second, and their effective temperature is as low as 1 mK. Specific feature of UCN consists of their nearly total elastic reflection from nuclear-optical potential of many materials at any incidence angle; therefore they could be stored in closed traps for many minutes, thus they could be used for extremely sensitive measurements. A fraction of UCN in the thermal neutron flux is as low as 10–11–10–12, and serious efforts are undertaken all over the world to produce UCN in larger amounts. UCN are widely used in precision particle physics experiments. Applications of UCN are emerging in surface and nanoparticle physics. Here we will focus on recent advances in the field.